Social media a critical introduction - Fuchs, Christian 1976- (Los Angeles Sage, 2014)
"Now more than ever, we need to understand social media - the good as well as the bad. We need critical knowledge that helps us to navigate the controversies and contradictions of this complex digital media landscape. Only then can we make informed judgments about what's happening in our media world, and why. Showing the reader how to ask the right kinds of questions about social media, Christian Fuchs takes us on a journey across social media, delving deep into case studies on Google, Facebook, Twitter, WikiLeaks and Wikipedia. The result lays bare the structures and power relations at the heart of our media landscape."--Publisher's description
What is a critical introduction to social media? -- What is social media? -- Social media as participatory culture -- Social media and communication power -- The power and political economy of social media -- Google : good or evil search engine? -- Facebook : a surveillance threat to privacy? -- Twitter : a new public sphere? -- WikiLeaks : can we make power transparent? -- Wikipedia : a new democratic form of collaborative work and production? -- Conclusion: Social media and its alternatives : towards a truly social media
Includes bibliographical references (pages [267]-288) and index.
Keywords: Social media